U.S. aid to Taiwan in education in the post-war period (1951–1965) - D Igorevich Petrov (RUDN Journal of World History, 2013)
The article considers the main stages and goals of U.S. aid to Taiwan in the field of education. Highlighted the leading role of the U.S. in the Taiwanese education system reform and training specialists abroad. Special attention is paid to the influence of changes in education on the process of post-war reconstruction of society in Taiwan.